The cutting edge : Khoe-San rock-markings at the Gestoptefontein-Driekuil engraving complex, North West Province, South Africa - Hollmann, Jeremy C., (Cambridge monographs in African archaeology ;, 2017)
Addresses rock engravings on the wonderstone hills just outside Ottosdal, South Africa. Much of the rock art has been destroyed due to mining activities, with very few records and the largest remaining outcrop is still threatened. The study hopes to bring this situation to the attention of the public and the heritage authorities.